Correlation between serum liver fibrosis markers and early gastroesophageal varices among patients with compensated liver cirrhosis: a cross-sectional analysis - Ling Mei; Ying Ma; Lili Zhao; Qingling Chen; Li Zhou; Hang Yang; Jie Liu; Jia Li (BMC Gastroenterology, 2022)
Abstract Background and aim Portal hypertension is a common complication of chronic liver diseases responsible for most liver cirrhosis consequences. In patients with portal hypertension, oesophagogastric variceal bleeding is a leading cause of death. Most research has focused on high-risk gastroesophageal varices and bleeding, with only a few studies on early varices. However, early intervention of gastroesophageal varices was found to better improve the prognosis and reduce mortality, but there is still no relevant research. Ultrasonic endoscopy is a combination of endoscopy and ultrasonic imaging. It can gastroscopically detect varices around the oesophagus and stomach and detect oesophageal collateral veins and perforating veins earlier, which is helpful for the early diagnosis of varices. Therefore, this study aimed to explore the correlation between serum fibrosis markers and early gastroesophageal varices in compensated cirrhosis patients. Methods This study included 791 patients with compensated cirrhosis. The selected patients were categorized into three groups. The early gastroesophageal varices group included patients with gastroesophageal varices found by endoscopic ultrasonography but not by gastroscopy. The no gastroesophageal varices group underwent endoscopic ultrasonography and gastroscopy without varices. In addition, gastroesophageal varices can be detected with both techniques. Multiple logistic regression analysis explored the association of serum fibrosis markers with early gastroesophageal varices. Results Among the 791 compensated liver cirrhosis patients, 198 patients were without gastroesophageal varices, 279 patients had early gastroesophageal varices, 314 patients had gastroesophageal varices, and both techniques could detect varices. There was a positive correlation between serum fibrosis markers and early gastroesophageal varices. In univariate logistic regression analysis, the patients with early gastroesophageal varices had lower platelet counts (P = 0.034) and higher aspartate aminotransferase (P = 0.046), total bilirubin (P = 0.041), hyaluronic acid (P < 0.001), laminin (P < 0.001), type III procollagen (P = 0.005), type IV collagen (P = 0.002), liver stiffness measurement (P = 0.001), APRI (P = 0.019) and FIB-4 (P = 0.002). Multivariate analysis showed that laminin (OR 1.011; 95% CI 1.004-1.017, P = 0.001) was an independent risk factor for predicting early gastroesophageal varices in compensated cirrhosis patients. Conclusion Higher laminin was independently associated with early gastroesophageal varices in compensated cirrhosis patients.